INVENTARISASI SERANGGA POLINATOR DI LAHAN PERTANIAN KACANG PANJANG (Vygnacylindrica) KOTA PEKANBARU DAN PENGEMBANGANNYA UNTUK SUMBER BELAJAR PADA KONSEP POLA INTERAKSI MAKHLUK HIDUP DI SMP - Meri Handani Handani; Mariani Natalina Linggasari Natalina Linggasari; Elya Febrita Febrita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The research was conducted to investigate diversity insectpollinators inlong beans (Vygna cylindrica) agricultural land Pekanbaru City in February to June, 2014. Research results are used to development of instructional media in the form of learning modules, student worksheet and interactivemediaofthe results ofthe inventoryof insectpollinators.This research was carried out by two stage that is the field research stage and media development stage. The research was conducted at 3 locations observation using total sampling at each station. Station I: located in the Tenayan Raya District, Seroja Kulim Street. Spacious long beans gardenrange between ± 60x 40 meters. Station II: located in the Rumbai District, Palas Village, Tengku Ibrahim Street Spacious long beans garden ±60x 40meters.Station III : located in the Tampan District, Bina Widya Street, faculty of Agriculture, University of Riau. Spacious longbeans gardenrange between±25x 30 meters the inventory of insect pollinators and environmental physical parameters include temperature, humidity and light intensity. The results showed that there are seven species of insect pollinator sare found in the long beans (Vygna cylindrica) agricultural land Pekanbaru City. Belonging to 6 families and 3 orders that the Order Hymenoptera Family Anthporidae (1 species), Family Apidae (2 species), Family Pesvinae (1 species). Order Diptera Family Syripidae (1 species) and Order Lepidoptera Family Lycanidae (1 species). temperatures ranged between from 25.4 to 31.9 OC, humidity ranged between 69-84% and light intensity ranges from 1673.2 to 3173.5 all physical environmental factors are still within the range of tolerance. Results of the study can be used as a source of learning namely learning modules, student worksheets and interactive media on the concept of interaction patterns of living creatures in Junior High School. Key Word: Type Insect Pollinator, Bean, Learning Resources.